The spin of dioxygen as the main factor in pulmonology and respiratory care - Boris Minaev (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2022)
Not many doctors are aware of the most important obstacle in pulmonology and respiration care which is determined by the electronic structure of molecular oxygen. In great contrast to a huge majority of chemically stable substances, the O2 molecule possesses two non-paired electrons with parallel spins.